Positive electrode active material and lithium secondary battery including same
By using LiF during the calcination of lithium manganese-based oxides, the development of phases is promoted at low temperature and the coating is formed, which solves the problem of insufficient phase development of lithium manganese-based oxides in lithium secondary batteries during low temperature synthesis, and improves electrochemical performance and stability.
Patent Information
- Application Number
- CN202411220912.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-27
- Filing Date
- 2024-09-02
- Publication Date
- 2025-04-29
AI Technical Summary
The positive electrode active substances used in existing lithium secondary batteries, especially lithium-rich lithium manganese-based oxides, have insufficient phase development during low temperature synthesis and low lithium ion conductivity, resulting in poor electrochemical performance and stability.
By using LiF during the calcination of lithium manganese-based oxides, the development of the phase is promoted at low temperatures, and a coating containing LiF is formed on the surface of lithium manganese-based oxides, reducing the specific surface area and reducing the side reaction between lithium manganese-based oxides and the electrolyte.
It has achieved the promotion of the specific phase development of lithium manganese-based oxides at relatively low temperatures, reduced manufacturing costs, inhibited overgrowth of primary particles, improved lithium ion conductivity, and improved electrochemical performance and stability.
Smart Images

Figure CN119905540A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material and a lithium secondary battery including the same. More specifically, the present invention relates to a positive electrode active material and a lithium secondary battery including the same. The positive electrode active material is a positive electrode active material comprising a lithium-rich lithium manganese-based oxide, which can be synthesized at a lower temperature than the existing synthesis process and can compensate for insufficient phase development and lithium ion conductivity when synthesized at low temperature. Background Art
[0002] Batteries use materials that can undergo electrochemical reactions at the positive and negative electrodes to store electrical energy. A typical example of such batteries is a lithium secondary battery that stores electrical energy through the chemical potential difference when lithium ions are inserted / released between the positive and negative electrodes.
[0003] The lithium secondary battery is prepared by using a substance capable of reversibly inserting and extracting lithium ions as a positive electrode active material and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.
[0004] Representative materials used as positive electrode active materials for lithium secondary batteries include lithium composite oxides. Examples of the lithium composite oxides include LiCoO2, LiMN2O4, LiNiO2, LiMnO2, or complex oxides of nickel, cobalt, manganese, or aluminum.
[0005] Among the above-mentioned positive electrode active materials, LiCoO2 is the most widely used due to its excellent life characteristics and charge and discharge efficiency, but its price competitiveness is limited due to the resource limitation of cobalt used as a raw material and its high price.
[0006] Lithium manganese-based oxides such as LiMnO2 and LiMN2O4 have the advantages of excellent thermal stability and low price, but have problems of small capacity and poor high temperature characteristics. In addition, LiNiO2-based positive electrode active materials have battery characteristics of high discharge capacity, but due to the cation mixing problem between lithium and transition metals, they are difficult to synthesize, resulting in major problems in rate performance.
[0007] Furthermore, depending on the severity of such cation mixing, a large amount of lithium byproducts are generated, most of which are composed of compounds of LiOH and Li2CO3, so when preparing the positive electrode slurry, it leads to gelation, or after preparing the electrode, it may become a cause of gas generation due to repeated charge and discharge. In addition, the residual Li2CO3 in the above lithium byproducts increases the swelling phenomenon of the monomer and becomes a cause of reducing the service life.
[0008] Various candidate materials are being discussed for compensating for the shortcomings of these existing positive electrode active materials.
[0009] For example, research is underway to use lithium-rich manganese-based oxides containing excess manganese in transition metals and a lithium content greater than the total content of transition metals as positive electrode active materials for lithium secondary batteries. Such lithium-rich manganese-based oxides are also called overlithi ated layered oxides (OLO).
[0010] Although the above OLO has the advantage of showing high capacity under high voltage working environment in theory, in reality, due to the excessive manganese contained in the oxide, its conductivity is relatively low, so there is a disadvantage that the rate performance of the lithium secondary battery using OLO is low. As mentioned above, when the rate performance is low, the charge / discharge capacity and life efficiency (cycle capacity retention) deteriorate during the cycle of the lithium secondary battery.
[0011] In order to solve the above problems, research has been conducted to change the composition of OLO, but these attempts have not yet reached commercialization level. Summary of the invention
[0012] Technical issues
[0013] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles plays a leading role in the market, and the demand for positive electrode active materials used in lithium secondary batteries is also constantly changing.
[0014] For example, in the prior art, lithium secondary batteries using lithium iron phosphate (LFP) are mainly used from the viewpoint of ensuring safety, etc., but recently, the use of nickel-based lithium composite oxides having a large energy capacity per unit weight compared to LFP has been expanded (of course, at present, relatively cheap LFP is still used to reduce costs).
[0015] In addition, nickel-based lithium composite oxides, which are mainly used as positive electrode active materials for high-capacity lithium secondary batteries in recent years, must use ternary metal elements such as nickel, cobalt and manganese or nickel, cobalt and aluminum. However, since cobalt is not only unstable in supply and demand but also too expensive compared to other raw materials, a positive electrode active material with a new composition that can reduce the cobalt content or does not contain cobalt is needed.
[0016] Taking the whole situation into consideration, although lithium-rich lithium manganese-based oxides can meet the expectations of the above-mentioned market, the above-mentioned lithium manganese-based oxides still have the limitation of lacking electrochemical performance or stability in replacing commercial positive electrode active materials such as ternary lithium composite oxides composed of nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA).
[0017] In addition, the lithium manganese-based oxide has a crystal structure different from the commercially available ternary lithium composite oxide composed of nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA), and in order to form a specific phase in the lithium manganese-based oxide, a temperature higher than the calcination temperature of the ternary lithium composite oxide is required. As described above, the increase in the calcination temperature required in the synthesis process has become a cause of increasing the manufacturing cost of the lithium manganese-based oxide.
[0018] If a specific phase cannot be formed in the lithium manganese-based oxide due to a low calcination temperature, the lithium ion conductivity decreases, resulting in a decrease in the overall electrochemical performance. In addition, as the specific surface area increases, the side reactions between the lithium manganese-based oxide and the electrolyte increase, which may reduce the stability.
[0019] The appropriate calcination temperature of the above-mentioned lithium manganese-based oxide requires a temperature of 850°C, preferably above 900°C. Under these harsh calcination conditions, the size of the primary particles constituting the above-mentioned lithium manganese-based oxide is too large than the particle size of the commercial ternary lithium composite oxide, resulting in an excessive reduction in specific surface area, thereby reducing rate performance, etc.
[0020] Therefore, an object of the present invention is to provide a positive electrode active material which can sufficiently induce the development of a specific phase in the lithium manganese-based oxide even at a relatively low temperature, thereby reducing the production cost of the lithium manganese-based oxide and suppressing excessive growth of primary particles.
[0021] In particular, the present invention aims to provide a positive electrode active material, which promotes phase development even at low temperatures and reduces the specific surface area to an appropriate level by using LiF during the calcination process of the above-mentioned lithium manganese-based oxide, thereby reducing the side reaction between the above-mentioned lithium manganese-based oxide and the electrolyte without reducing the rate performance.
[0022] Another object of the present invention is to provide a positive electrode active material capable of compensating for the insufficient lithium ion conductivity of the lithium manganese-based oxide by forming a coating layer containing LiF on the surface of the lithium manganese-based oxide after the low-temperature synthesis.
[0023] Another object of the present invention is to provide a positive electrode comprising a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material defined herein.
[0024] In addition, an object of the present invention is to provide a lithium secondary battery having improved capacity and rate performance compared to a lithium secondary battery using existing OLO as a positive electrode active material by using the positive electrode defined herein.
[0025] The purpose of the present invention is not limited to the purpose mentioned above, and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.
[0026] Solutions to the problem
[0027] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material including a lithium manganese-based oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved.
[0028] In the commonly commercialized ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), the phase belonging to the R3-m space group exists as a single phase. However, the lithium-rich lithium manganese-based oxide defined in this article is characterized in that the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group are solid-dissolved.
[0029] In one embodiment, a fluorine-containing coating portion exists in at least a portion of the surface of the lithium manganese-based oxide. The coating portion may include LiF.
[0030] Preferably, when the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα radiation, the full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ=18° to 19° is a The full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ=44° to 45° is greater than or equal to 0.14 and less than or equal to 0.221. b is greater than or equal to 0.31 and less than 0.641, and when the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα radiation, the full width at half maximum (FWHM) of the diffraction peak that appears in the region of 2θ=44° to 45° is b The full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ = 18° to 19° a Ratio FWHM b / FWHM a Greater than 1.738 and less than or equal to 2.665.
[0031] In one embodiment, the lithium manganese-based oxide may exist in the form of secondary particles formed by agglomeration of a plurality of primary particles, and the LiF concentration on the surface of the secondary particles may be higher than the LiF concentration in the center of the secondary particles.
[0032] The lithium manganese-based oxide may exist in the form of secondary particles formed by agglomeration of a plurality of primary particles, and may have a fluorine concentration gradient decreasing from the surface of the secondary particles toward the center of the secondary particles along grain boundaries between the primary particles.
[0033] In one embodiment, the lithium manganese-based oxide may be represented by the following Chemical Formula 1 or Chemical Formula 1-1.
[0034] [Chemical formula 1]
[0035] Li(Li a M1 x M2 y ) 2-b X b
[0036] (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 does not overlap with M1, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, and 0 <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)
[0037] [Chemical formula 1-1]
[0038] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'
[0039] (wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 does not overlap with M1, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7、0≤c≤0.1、0<a'≤1、0≤b'≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1)
[0040] Furthermore, according to another aspect of the present invention, a positive electrode including the positive electrode active material is provided.
[0041] According to still another aspect of the present invention, there is provided a lithium secondary battery using the positive electrode.
[0042] Effects of the Invention
[0043] According to the present invention, the limitations of existing lithium-rich lithium manganese-based oxides which are still inferior in electrochemical performance and / or stability compared with commercial ternary lithium composite oxides composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) can be improved.
[0044] Specifically, according to the present invention, when calcining the lithium manganese-based oxide, by using LiF, the development of the specific phase of the above-mentioned lithium manganese-based oxide can be fully promoted even at low temperatures, the specific surface area can be reduced to an appropriate level, and the side reaction between the above-mentioned lithium manganese-based oxide and the electrolyte can be reduced without reducing the rate performance.
[0045] As described above, according to the present invention, the development of a specific phase can be induced in the lithium manganese-based oxide even at a relatively low temperature, thereby reducing the production cost of the lithium manganese-based oxide while suppressing excessive growth of primary particles.
[0046] In addition, according to the present invention, the LiF used during calcination forms a coating layer containing LiF on the surface of the lithium manganese-based oxide instead of being doped into the lithium manganese-based oxide to compensate for the insufficient lithium ion conductivity of the lithium manganese-based oxide. In particular, according to the present invention, the hydroxide precursor is converted into an oxide precursor by a roasting treatment before calcination, and then mixed with a lithium raw material and LiF for calcination, thereby effectively preventing LiF from being doped into the lithium manganese-based oxide during the calcination process.
[0047] In addition, in the present invention, since LiF used in the calcination process exists in the form of a coating on the surface of the lithium manganese-based oxide, the insufficient lithium ion conductivity of the lithium manganese-based oxide can be compensated.
[0048] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a graph showing changes in the content of fluorine element according to the XPS analysis of Experimental Example 4 and depending on the etching depth. DETAILED DESCRIPTION
[0050] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.
[0051] Hereinafter, a positive electrode active material including a lithium-rich lithium manganese-based oxide and a lithium secondary battery including the positive electrode active material according to the present invention will be described in more detail.
[0052] Positive active material
[0053] According to one aspect of the present invention, there is provided a positive electrode active material, the positive electrode active material comprising a lithium manganese-based oxide in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group are solid-dissolved.
[0054] The phase belonging to the C2 / m space group and the phase belonging to the R3-m space group can be distinguished not only by the composition of each phase, but also by the specific peaks of each phase during XRD analysis. For example, the peak specific to the phase belonging to the C2 / m space group may appear in the region of 2θ=20.8±1°, and the peak specific to the phase belonging to the R3-m space group may appear in the region of 2θ=18.6±1°.
[0055] The lithium manganese-based oxide is a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, and the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group coexist in the lithium manganese-based oxide. In addition, the lithium manganese-based oxide is different from a composite oxide having a spinel crystal structure belonging to the Fd-3m space group (for example, LiMN2O4 or an oxide having a composition similar thereto).
[0056] The lithium manganese-based oxide contains at least lithium, manganese and a transition metal. The transition metal may include at least one selected from nickel, cobalt and aluminum. In addition, the lithium manganese-based oxide may include lithium, nickel and manganese, and may optionally further include a transition metal other than nickel.
[0057] At this time, the content of lithium present in the above-mentioned lithium manganese-based oxide is greater than the sum of the contents of other transition metals (generally, the molar ratio of lithium to all metal elements except lithium in the lithium manganese-based oxide (lithium / metal molar ratio (Li / Metal molar ratio) is greater than 1), so it is also called lithium-rich layered oxide (overlithiated layered oxide; OLO).
[0058] In addition, since the content of manganese in the lithium manganese-based oxide is greater than the content of other transition metals, the lithium manganese-based oxide is also called a layered oxide with excess lithium and manganese.
[0059] Generally speaking, considering that the manganese content in the total metal elements other than lithium in the commercial nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is less than 20 mol%, the above-mentioned lithium manganese-based oxide has a relatively high ratio of manganese in the total metal elements (for example, more than 50 mol%, more than 52 mol%, more than 53 mol% or more than 55 mol%) compared with the commercial ternary lithium composite oxide.
[0060] Furthermore, considering that the content of nickel in the total metal elements other than lithium in the commercialized nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) ternary lithium composite oxide is more than 60 mol% (more than 80 mol% in the case of high-nickel lithium composite oxides), the above-mentioned lithium manganese-based oxide has a relatively low ratio of nickel in the total metal elements (for example, less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%) compared with the commercialized ternary lithium composite oxide.
[0061] There is also a difference that the lithium / metal molar ratio measured from the lithium manganese-based oxide defined herein is greater than the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA). For example, the lithium / metal molar ratio of a ternary lithium composite oxide such as nickel cobalt manganese (NCM) or nickel cobalt aluminum (NCA) appears to be close to 1. On the other hand, the lithium / metal molar ratio of the lithium manganese-based oxide defined herein is greater than 1, preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.
[0062] Therefore, herein, the lithium manganese-based oxide may be defined as a composite oxide in which the manganese content in the metal elements other than lithium is 50 mol % or more, or may be defined as a composite oxide in which the manganese content in the metal elements other than lithium is 50 mol % or more and the nickel content is less than 50 mol %.
[0063] In addition, the lithium manganese-based oxide herein has a molar ratio of lithium to the total metal elements other than lithium greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, and is defined as a composite oxide in which the manganese content in the total metal elements other than lithium is 50 mol% or more, or a composite oxide in which the molar ratio of lithium to the total metal elements other than lithium is greater than 1, or is 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5, the manganese content in the total metal elements other than lithium is 50 mol% or more, and the nickel content is less than 50 mol%.
[0064] Despite the above-mentioned difference in composition, the above-mentioned lithium manganese-based oxide can also be used as a composite metal oxide capable of intercalating / deintercalating lithium ions.
[0065] The lithium composite oxide contained in the positive electrode active material as defined herein may be present as particles including at least one primary particle.
[0066] When the lithium manganese-based oxide exists as a single primary particle, the lithium composite oxide may be referred to as a single particle. On the other hand, when the lithium manganese-based oxide exists as an aggregate formed by agglomerating a plurality of primary particles, the lithium composite oxide may be referred to as a secondary particle.
[0067] The positive electrode active material may include at least one selected from the group consisting of a lithium manganese-based oxide present as a single particle and a lithium manganese-based oxide present as a secondary particle formed by agglomerating a plurality of primary particles.
[0068] The primary particles constituting the above-mentioned lithium manganese-based oxide may have a rod (rod) shape, an elliptical shape and / or an irregular shape. In addition, unless specifically designed during the manufacturing process, primary particles of various shapes exist in the same positive electrode active material. In addition, the above-mentioned primary particles refer to particle units that do not appear to have grain boundaries when observed with a scanning electron microscope at a magnification of 5000 to 20000 times.
[0069] The average particle size of the primary particles constituting the lithium manganese-based oxide defined herein may be 0.05 μm to 5 μm, 0.05 μm to 1.0 μm or 0.25 μm to 0.75 μm. At this time, as the average particle size of the primary particles, the average value of the length in the major axis direction and the length in the minor axis direction of the primary particles ([major axis length + minor axis length] / 2) may be used.
[0070] When the average particle size of the primary particles is less than 0.05 μm, the specific surface area of the lithium manganese-based oxide (secondary particles) composed of the primary particles is large. In this case, the possibility of causing a side reaction between the lithium manganese-based oxide and the electrolyte during storage or operation of the lithium secondary battery increases.
[0071] On the other hand, when the average particle size of the primary particles is greater than 5 μm, the growth of the primary particles is excessively induced, so the diffusion path of lithium ions in the primary particles becomes longer. When the diffusion path of lithium ions in the primary particles is too long, the mobility of lithium ions in the primary particles and the diffusivity of lithium ions through the primary particles are reduced, which becomes a cause of increasing the resistance of the lithium composite oxide (secondary particles) composed of the primary particles.
[0072] Therefore, in order to reduce the specific surface area of the lithium manganese-based oxide while preventing the mobility of lithium ions in the primary particles and the diffusivity of lithium ions through the primary particles from decreasing, the average particle size of the primary particles is preferably 0.05 μm to 5 μm, 0.1 μm to 1.0 μm or 0.25 μm to 0.75 μm.
[0073] When the lithium manganese-based oxide exists as secondary particles formed by the aggregation of multiple primary particles, the average particle size of the secondary particles can be 0.5μm to 15μm, 1.0μm to 15μm, 2.0μm to 15μm, 3.0μm to 15μm, 4.0μm to 15μm or 5.0μm to 15μm. The average particle size of the secondary particles can vary according to the number of the primary particles constituting the secondary particles. The average particle size (D50) of the secondary particles can be measured using a laser diffraction method. For example, after the secondary particles are dispersed in a dispersion medium, they are introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), irradiated with ultrasonic waves of about 28kHz at a power of 60W, and then after obtaining a volume cumulative particle size distribution chart, the particle size equivalent to 50% of the volume cumulative amount is obtained to achieve measurement.
[0074] Unless otherwise defined, the term "surface of the primary particle" as used herein refers to the outer surface of the primary particle exposed to the outside. Similarly, the term "surface of the secondary particle" as used herein refers to the outer surface of the secondary particle exposed to the outside. In this case, the "surface of the secondary particle" formed by the agglomeration of multiple primary particles is equivalent to the exposed surface of the primary particle existing on the surface of the secondary particle.
[0075] In addition, unless otherwise defined, the term "surface portion of a particle" as used herein refers to a region relatively close to the "outermost surface" of a particle, and "center portion of a particle" refers to a region relatively close to the "exact center" of a particle compared to the above-mentioned "surface portion". Therefore, the "surface portion of a primary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned primary particle, and the "center portion of a primary particle" refers to a region relatively close to the "exact center" of the above-mentioned primary particle compared to the above-mentioned "surface portion". Similarly, the "surface portion of a secondary particle" refers to a region relatively close to the "outermost surface" of the above-mentioned secondary particle, and the "center portion of a secondary particle" refers to a region relatively close to the "exact center" of the above-mentioned secondary particle compared to the above-mentioned "surface portion".
[0076] At this time, a region other than the “surface portion of the particle” within any particle can be defined as the “center portion of the particle”.
[0077] For example, when the radius of the primary particle is r, the region at a distance of 0r to 0.5r from the surface of the primary particle can be defined as the surface portion of the primary particle, and the region at a distance of 0r to 0.5r from the exact center of the primary particle can be defined as the central portion of the primary particle. If the radius of the primary particle is 0.5 μm, the surface portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the surface of the primary particle, and the central portion of the primary particle can be defined as the region at a distance of 0 μm to 0.25 μm from the exact center of the primary particle.
[0078] In addition, as needed, when the radius of the above-mentioned primary particle is r, the area with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned primary particle can be defined as the surface part of the above-mentioned primary particle, and the area with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned primary particle can be defined as the central part of the above-mentioned primary particle.
[0079] Similarly, when the radius of the secondary particle is r, the region at a distance of 0r to 0.5r from the surface of the secondary particle can be defined as the surface portion of the secondary particle, and the region at a distance of 0r to 0.5r from the exact center of the secondary particle can be defined as the central portion of the secondary particle. If the radius of the secondary particle is 2.0 μm, the surface portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the surface of the secondary particle, and the central portion of the secondary particle can be defined as the region at a distance of 0 μm to 1.0 μm from the exact center of the secondary particle.
[0080] In addition, as needed, when the radius of the above-mentioned secondary particle is r, the region with a distance of 0r to 0.1r or 0r to 0.2r from the surface of the above-mentioned secondary particle can be defined as the surface portion of the above-mentioned secondary particle, and the region with a distance of 0r to 0.2r or 0r to 0.5r from the exact center of the above-mentioned secondary particle can be defined as the central portion of the above-mentioned secondary particle.
[0081] The lithium manganese-based oxide defined herein may be a lithium-rich lithium manganese-based oxide represented by the following Chemical Formula 1. The composition represented by the following Chemical Formula 1 may represent an average composition reflecting the composition of the coating layer present in at least a portion of the surface of the lithium manganese-based oxide.
[0082] [Chemical formula 1]
[0083] Li(Li a M1 x M2 y ) 2-b X b
[0084] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, M2 and M1 are not repeated, X is a halogen that can replace at least a part of the oxygen present in the above-mentioned lithium manganese-based oxide, and 0 <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1。
[0085] As the kind of halogen that can be used as X, referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably F can be used.
[0086] In another embodiment, the lithium manganese-based oxide may be represented by the following chemical formula 1-1. The composition represented by the following chemical formula 1-1 may represent an average composition reflecting the composition of the coating layer present in at least a portion of the surface of the lithium manganese-based oxide.
[0087] [Chemical formula 1-1]
[0088] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b'
[0089] Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and N, M2 does not overlap with M1, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the above-mentioned lithium manganese-based oxide, <r≤0.7、0≤c≤0.1、0<a'≤1、0≤b'≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1。
[0090] As the kind of halogen that can be used as X and X', referring to the periodic table, F, Cl, Br and / or I etc. can be used, and preferably, F can be used.
[0091] In the above Chemical Formula 1 and the above Chemical Formula 1-1, when M1 is Ni, M2 may include Mn, and when M1 is Mn, M2 may include Ni. In addition, when M1 is Ni and Mn, M2 may not exist, or, if present, may be an element other than Ni and Mn.
[0092] That is, when M1 is Ni, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, and even more preferably at least one selected from P, B and Si) and Mn.
[0093] When M1 is Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd (preferably at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably at least one selected from P, B and Si) and Ni.
[0094] When M1 is Ni and Mn, M2 may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, preferably, may include at least one selected from Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo and W, more preferably, may include at least one selected from Co, P, B, Si, Ti, Zr and W, even more preferably, may include at least one selected from P, B and Si.
[0095] The lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may optionally include cobalt. In addition, when the above lithium manganese-based oxide includes cobalt, the molar number of the above cobalt relative to the molar number of the entire metal element in the above lithium manganese-based oxide may be 20% or less, preferably, 15% or less, and more preferably, 10% or less. In another case, the above lithium manganese-based oxide may have a cobalt-free composition that does not contain cobalt.
[0096] The lithium / metal molar ratio measured from the lithium manganese-based oxide represented by the above chemical formula 1 or the above chemical formula 1-1 may be greater than 1, preferably, it may be 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5. Only when the lithium / metal molar ratio measured from the above lithium manganese-based oxide is at least greater than 1, a lithium-rich lithium manganese-based oxide can be formed. In addition, in order to allow the above lithium manganese-based oxide to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, and at the same time exert a high capacity under a high voltage working environment, the lithium / metal molar ratio of the above lithium manganese-based oxide is preferably 1.1 to 1.6, 1.1 to 1.5, 1.2 to 1.6 or 1.2 to 1.5.
[0097] In addition, in order to properly form a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, the manganese content in the entire metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is preferably 50 mol% or more.
[0098] In order to make the above-mentioned lithium manganese-based oxide have OLO characteristics showing high capacity under a high voltage operating environment, the content of manganese in the entire metal elements except lithium present in the above-mentioned lithium manganese-based oxide can be 50 mol% or more and less than 80 mol%, 51 mol% or more and less than 80 mol%, 52 mol% or more and less than 80 mol%, 53 mol% or more and less than 80 mol%, 54 mol% or more and less than 80 mol%, 55 mol% or more and less than 80 mol%, 50 mol% or more and 75 mol%, 51 mol% or more and 75 mol%, 52 mol% or more and 75 mol%, 53 mol% or more and 75 mol%, 54 mol% or more and 75 mol%, 55 mol% or more and 75 mol%,
[0099] When the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, a phase change may occur during the formation and / or operation of the lithium secondary battery due to the movement of the transition metal (especially manganese) in the above-mentioned lithium manganese-based oxide. This phase change occurs at random positions in the above-mentioned lithium manganese-based oxide, which may lead to a reduction in charge / discharge capacity or voltage decay during the cycle of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material. In addition, when the manganese content in the above-mentioned lithium manganese-based oxide exceeds 80 mol%, the above-mentioned lithium manganese-based oxide may exhibit the characteristics of a composite oxide (for example, LiMN2O4 or an oxide having a similar composition thereto) having a spinel crystal structure belonging to the Fd-3m space group.
[0100] In order to properly form a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are solid-dissolved, the content of nickel in the entire metal elements other than lithium present in the lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 can be less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 42 mol% or less than 40 mol%.
[0101] When the nickel content in the above-mentioned lithium manganese-based oxide is above 50 mol%, it is difficult to fully form the C2 / m phase, or the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group may not form a sufficient solid solution, resulting in phase separation during the formation and / or operation of the lithium secondary battery.
[0102] Generally, in a commercially available ternary lithium composite oxide composed of nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA), a phase belonging to the R3-m space group exists as a single-phase.
[0103] On the other hand, the lithium-rich lithium manganese-based oxide represented by the above Chemical Formula 1 or the above Chemical Formula 1-1 is composed of rLi2MnO3-c X' c The oxides of the phase belonging to the C2 / m space group (hereinafter referred to as "C2 / m phase") and (1-r)Li a M1 x M2 y O 2-b X b The composite oxide exists in which the oxide of the phase belonging to the R3-m space group (hereinafter referred to as "R3-m phase") is solid-solved. In the present invention, the solid-solution of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group means that the oxide of the C2 / m phase and the oxide of the R3-m phase exist in a state of forming a solid solution.
[0104] In this case, a composite oxide in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group are simply physically and / or chemically combined or attached does not correspond to a solid solution as defined herein.
[0105] For example, coating a surface with a metal oxide having a phase belonging to the C2 / m space group with a metal oxide having a phase belonging to the R3-m space group by mixing a metal oxide having a phase belonging to the C2 / m space group and a metal oxide having a phase belonging to the R3 space group does not correspond to the solid solution defined in this article.
[0106] In addition, in the lithium manganese-based oxide represented by the above chemical formula 1-1, when r exceeds 0.7, rLi2MnO as an oxide of the C2 / m phase in the above lithium manganese-based oxide 3-c X' c The ratio of R3-m phase oxide to C2-m phase oxide is excessively increased, which may increase the irreversible capacity and resistance of the positive electrode active material, thereby reducing the discharge capacity. That is, in order to fully activate the C2 / m phase oxide with relatively high resistance in the above-mentioned lithium manganese-based oxide to improve the surface dynamics, the R3-m phase oxide is preferably present in a predetermined ratio or more.
[0107] In one embodiment, a fluorine-containing coating portion may be formed on at least a portion of the surface of the lithium manganese-based oxide. In the case where the lithium manganese-based oxide is a secondary particle formed by agglomeration of a plurality of primary particles, the coating portion may cover at least a portion of the surface of the primary particle and / or the secondary particle. By forming a fluorine-containing coating portion on the surface of the lithium manganese-based oxide, the side reaction with the electrolyte occurring on the surface of the lithium manganese-based oxide is reduced, and at the same time, the charge transfer and / or diffusivity (i.e., surface dynamics) of lithium ions on the surface of the lithium manganese-based oxide can be alleviated and / or prevented from decreasing.
[0108] The surface where adjacent primary particles in the secondary particles are connected can be called the interface between the primary particles, and the interface between the primary particles can be defined as the grain boundary between the primary particles. In addition, the primary particles can be separated from adjacent primary particles inside the secondary particles to form internal voids.
[0109] The coating layer is defined as a region where fluorine exists on the surface of the primary particle and / or the secondary particle, and the coating portion may be formed in whole or in part on the surface of the primary particle and / or the secondary particle. When the coating portion is formed on the surface of the primary particle and / or the secondary particle, the shape of the coating may be called an island.
[0110] Furthermore, fluorine may exist in a state of being physically and / or chemically bonded in the form of a chemical substance on the surface of the primary particles and / or the secondary particles, or may exist in a state of being partially solid-solved.
[0111] As fluorine diffuses from the surface of the secondary particle toward the center of the secondary particle along the grain boundary between the primary particles, the coating layer existing inside the secondary particle may be formed.
[0112] Specifically, the main compound (e.g., fluorine-containing compound) constituting the coating portion may exist in a state of diffusion from the surface portion of the secondary particle to the center portion of the secondary particle. As the coating portion diffuses from the surface portion of the secondary particle to the center portion of the secondary particle, the element (e.g., fluorine) mainly contained in the coating portion may present a concentration gradient that decreases from the surface portion of the secondary particle to the center portion of the secondary particle.
[0113] In one embodiment, the coating layer may include a fluorine-containing compound. In this case, a representative example of the fluorine-containing compound is LiF. After the mixture of the oxide precursor of the lithium manganese-based oxide, the lithium raw material and LiF is subjected to low-temperature heat treatment, LiF may exist in a state of forming a coating layer on the surface of the lithium manganese-based oxide.
[0114] For example, by mixing the above-mentioned lithium manganese-based oxide and a fluorine-containing polymer (for example, PVDF, PTFE, etc.) and then heat-treating the mixture, LiF can be formed on the surface of the above-mentioned lithium manganese-based oxide. As mentioned above, the fluorine coating using the fluorine-containing polymer is performed after the hydroxide precursor or the oxide precursor is calcined into the above-mentioned lithium manganese-based oxide. Therefore, it not only does not help to reduce the calcination temperature of the existing synthesis process, but also has nothing to do with the phase development of the above-mentioned lithium manganese-based oxide.
[0115] In the above-mentioned positive electrode active material, LiF may be present in a content of 0.5 mol% to 1.5 mol%. The LiF content in the above-mentioned positive electrode active material being less than 0.5 mol% means that the LiF content used in the calcination process of the precursor in the oxide state of the above-mentioned lithium manganese-based oxide is too little. In this case, the phase development of the above-mentioned lithium manganese-based oxide cannot be fully induced during the calcination process. On the other hand, the LiF content in the above-mentioned positive electrode active material being greater than 0.5 mol% means that the LiF content used in the calcination process of the precursor in the oxide state of the above-mentioned lithium manganese-based oxide is too much. In this case, the LiF content present on the surface of the above-mentioned lithium manganese-based oxide excessively increases, changing the surface resistance of the above-mentioned lithium manganese-based oxide, thereby possibly reducing the overall electrochemical performance of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material. It can be calculated based on the content of LiF present in the above-mentioned positive electrode active material mixed with the oxide precursor of the above-mentioned lithium manganese-based oxide.
[0116] In addition, the average thickness of the coating portion present on the surface of the lithium manganese-based oxide is 5 nm to 100 nm, 5 nm to 50 nm, or 5 nm to 30 nm. The thickness of the coating portion present on the surface of the lithium manganese-based oxide can be measured by performing XPS analysis on fluorine as a target element in the lithium manganese-based oxide (for example, refer to Figure 1 In the case where the average etching rate of the XPS analysis device measuring the F depth profile is 0.3 nm / 1 second, when fluorine is significantly detected within the etching time of 0 to 30 seconds, the thickness of the coating portion containing fluorine can be calculated to be 9 nm. Similarly, when fluorine is significantly detected within the etching time of 0 to 100 seconds, the thickness of the coating portion containing fluorine can be calculated to be 30 nm.
[0117] If fluorine is detected inside the secondary particles because LiF also exists at the grain boundaries between the primary particles, the thickness of the coating portion present on the surface of the lithium manganese-based oxide can be defined as the thickness from the outermost surface of the secondary particles to the depth at which the fluorine concentration begins to remain constant. In addition, the average thickness of the coating portion present on the surface of the lithium manganese-based oxide can be calculated as the average value of the thicknesses measured by repeating the XPS analysis multiple times (more than 10 times).
[0118] The fluorine content in the above-mentioned coating portion calculated by the above-mentioned XPS analysis can be 2 atomic % to 10 atomic %. The fluorine content in the above-mentioned coating portion less than 2 atomic % means that the content of LiF used in the calcination process of the precursor in the oxide state of the above-mentioned lithium manganese-based oxide is too little. In this case, the phase development of the above-mentioned lithium manganese-based oxide cannot be fully induced during the calcination process. On the other hand, the fluorine content in the above-mentioned coating portion greater than 10 atomic % means that the content of LiF used in the calcination process of the precursor in the oxide state of the above-mentioned lithium manganese-based oxide is too much. In this case, the LiF content present on the surface of the above-mentioned lithium manganese-based oxide excessively increases, changing the surface resistance of the above-mentioned lithium manganese-based oxide, thereby possibly reducing the overall electrochemical performance of the lithium secondary battery using the above-mentioned lithium manganese-based oxide as the positive electrode active material.
[0119] In addition, the LiF present in the coating portion may be used as a lithium ion diffusion path, that is, a two-dimensional and / or three-dimensional path for lithium ions to diffuse in the lithium manganese-based oxide.
[0120] As lithium ion diffusion paths are formed in the lithium manganese-based oxide, resistance to movement of lithium ions through the lithium manganese-based oxide is reduced, thereby contributing to improved rate performance of a lithium secondary battery using the lithium manganese-based oxide as a positive electrode active material.
[0121] The BET specific surface area of the positive electrode active material according to the present invention can be 1.6 m 2 / g or more and 3.2m 2 / g or less, 1.6m 2 / g or more and 3.1m 2 / g or less, 1.7m 2 / g or more and 3.1m 2 / g or less or 1.72m 2 / g or more and 3.09m 2 / g or less.
[0122] According to the present invention, LiF is used when calcining the lithium manganese-based oxide, so that the phase development can be promoted even at a low temperature, and the side reaction between the lithium manganese-based oxide and the electrolyte can be reduced by reducing the specific surface area.
[0123] Furthermore, as defined herein, when the oxide precursor of the lithium manganese-based oxide is calcined at a low temperature, when a positive electrode active material using LiF is subjected to X-ray diffraction analysis using Cu-Kα rays, the following characteristics may be exhibited.
[0124] When the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα radiation, the full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ=18° to 19° is aGreater than or equal to 0.14 and less than 0.221, or greater than or equal to 0.14 and less than or equal to 0.205, and the full width at half maximum FWHM of the diffraction peak appearing in the region of 2θ = 44° to 45° b Greater than or equal to 0.31 and less than 0.641, greater than or equal to 0.31 and less than 0.614, or greater than or equal to 0.31 and less than or equal to 0.516.
[0125] In addition, compared with the case where LiF is not used during low-temperature calcination, the half-maximum full width of the diffraction peak appearing in the region of 2θ=18° to 19° and the half-maximum full width of the diffraction peak appearing in the region of 2θ=44° to 45° may both be reduced. Compared with the case where LiF is not used during low-temperature calcination, the half-maximum full width of the diffraction peak appearing in the region of 2θ=18° to 19° and the half-maximum full width of the diffraction peak appearing in the region of 2θ=44° to 45° may both be reduced, which means that the phase development specific to the above-mentioned lithium manganese-based oxide is promoted.
[0126] When the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα radiation, the full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ=44° to 45° is b The full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ = 18° to 19° a Ratio FWHM b / FWHM a It may be greater than 1.738 and less than or equal to 2.665, or greater than or equal to 2.214 and less than or equal to 2.665.
[0127] In addition, when a coating layer containing LiF is present on the surface of the lithium manganese-based oxide, LiF reacts with deionized water during pH titration to generate HF, thereby causing a reversible reaction in which HF decomposes Li2CO3 dissolved in the deionized water.
[0128] <Li2CO3 decomposition reaction of LiF>
[0129] LiF+H2O→LiOH+HF
[0130] 2HF+Li2CO3→2LiF+CO2+H2O
[0131] That is, as the content of LiF on the surface of the positive electrode active material (lithium manganese-based oxide) increases, the content of LiOH measured during pH titration increases, while the content of Li2CO3 decreases. Therefore, if LiF is decomposed and doped into the lithium manganese-based oxide rather than coated on the surface of the lithium manganese-based oxide during the heat treatment process, the content changes of LiOH and Li2CO3 according to the above-mentioned reversible reaction are not observed.
[0132] According to the reversible reaction of LiF described above, the content of LiOH measured by neutralization titration of the positive electrode active material defined in this article may be greater than the content of Li2CO3.
[0133] Lithium secondary battery
[0134] According to another aspect of the present invention, a positive electrode including a positive electrode collector and a positive electrode active material layer formed on the positive electrode collector can be provided. The positive electrode active material layer can include a lithium manganese-based oxide having a coating portion formed on at least a portion of the surface according to some embodiments of the present invention as a positive electrode active material.
[0135] Therefore, the detailed description of the lithium manganese-based oxide will be omitted, and only the remaining components not mentioned above will be described below. In addition, for the sake of convenience, the lithium manganese-based oxide will be referred to as a positive electrode active material.
[0136] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or the surface of aluminum or stainless steel may be treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine concavoconvexities may be formed on the surface of the current collector to improve the binding force of the positive electrode active material. For example, it may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a nonwoven body.
[0137] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition including the positive electrode active material, a conductive material, and optionally a binder as required, on the positive electrode current collector.
[0138] In this case, the content of the positive electrode active material can be 80 wt % to 99 wt %, more specifically 85 wt % to 98.5 wt % relative to the total weight of the positive electrode active material layer. When the positive electrode active material is included in the above content range, excellent capacity performance can be shown, but it is not limited thereto.
[0139] The above-mentioned conductive materials are used to impart conductivity to the electrode. In the battery formed, as long as they do not cause chemical changes and have electronic conductivity, they can be used without limitation. As specific examples, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and one of them or a mixture of two or more thereof can be used. The above-mentioned conductive material may be included in an amount of 0.1% to 15% by weight relative to the total weight of the positive electrode active material layer.
[0140] The above-mentioned binder plays a role in improving the adhesion between multiple positive electrode active material particles and the bonding force between the positive electrode active material and the collector. As a specific example, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile (polyacrylonitrile), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated ethylene propylene diene rubber, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, etc., can be used. One or a mixture of two or more thereof. Relative to the total weight of the positive electrode active material layer, 0.1% to 15% by weight of the above-mentioned binder may be included.
[0141] In addition to using the above-mentioned positive electrode active material, the above-mentioned positive electrode can be prepared according to a common positive electrode preparation method. Specifically, it can be prepared by coating a positive electrode slurry composition on a positive electrode collector and then drying and rolling it. The above-mentioned positive electrode slurry composition is prepared by dissolving or dispersing the above-mentioned positive electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent.
[0142] The above-mentioned solvent may be a solvent commonly used in the art, and examples thereof include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone or water, and a mixture of one or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, the amount of the above-mentioned solvent used is sufficient to dissolve or disperse the above-mentioned positive electrode active material, conductive material and binder and have a viscosity that can show excellent thickness uniformity when applied to prepare the positive electrode.
[0143] Furthermore, in another embodiment, the positive electrode may be prepared by casting the positive electrode slurry composition on a separate support, and then laminating a thin film obtained by peeling the support on a positive electrode collector.
[0144] In addition, according to another aspect of the present invention, an electrochemical device comprising the positive electrode described above can be provided. Specifically, the electrochemical device described above can be a battery, a capacitor, etc., and more specifically, can be a lithium secondary battery.
[0145] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode disposed opposite to the positive electrode, and a separation membrane and an electrolyte disposed between the positive electrode and the negative electrode. The positive electrode is the same as the above description, so for convenience, the specific description is omitted, and only the remaining configuration not described above is described below.
[0146] The lithium secondary battery may further include: a battery container for accommodating the electrode assembly of the positive electrode, the negative electrode and the separation membrane; and a sealing member for sealing the battery container.
[0147] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0148] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can usually have a thickness of 3 μm to 500 μm. Similar to the positive electrode current collector, the binding force of the negative electrode active material can be strengthened by forming fine concave and convex on the surface of the collector. For example, it can be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, and a non-woven body.
[0149] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition including the negative electrode active material and a conductive material and optionally including a binder as required on the negative electrode collector.
[0150] As the negative electrode active material, a compound capable of reversibly inserting and extracting lithium can be used. Specific examples include carbon materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; and SiO β(0<β<2), SnO2, vanadium oxide, lithium vanadium oxide, metal oxides capable of being doped and dedoped with lithium; or composites containing the above metal compounds and carbon materials such as Si-C composites or Sn-C composites, etc., and one or a mixture of two or more of them can be used. In addition, as the above-mentioned negative electrode active material, a metal lithium film can also be used. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Representative low-crystalline carbons are soft carbon and hard carbon, and representative high-crystalline carbons are amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite (Kishgraphite), pyrolytic carbon (pyrolytic carbon), mesophase pitch based carbon fiber (mesophase pitch based carbon fiber), mesophase carbon microbeads (meso-carbon microbeads), mesophase pitch (Mesophase pitches) and petroleum or coal tar pitch derived cokes (petroleum or coal tar pitch derived cokes) and other high-temperature calcined carbons.
[0151] The negative electrode active material layer may contain 80 wt % to 99 wt % of the negative electrode active material, based on the total weight of the negative electrode active material layer.
[0152] The binder is a component that helps to bind the conductive material, the active material and the collector. Usually, based on the total weight of the negative electrode active material layer, 0.1 wt % to 10 wt % of the binder can be added. Examples of such binders include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber, sulfonated ethylene propylene diene rubber, styrene butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0153] The conductive material is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the conductive material can be added in an amount of 10% by weight or less, preferably 5% by weight or less. There are no particular restrictions on such conductive materials as long as they do not induce chemical changes in the corresponding battery and have conductivity. For example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. can be used.
[0154] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition on a negative electrode collector and drying it, wherein the negative electrode slurry composition is prepared by dissolving or dispersing the negative electrode active material in a solvent and selectively dissolving or dispersing a binder and a conductive material in a solvent, or by casting the negative electrode slurry composition on a separate support and laminating a thin film obtained by peeling off the support on the negative electrode collector.
[0155] On the other hand, in the above-mentioned lithium secondary battery, the separation membrane is used to separate the negative electrode and the positive electrode and provide a mobile channel for lithium ions. As long as the separation membrane commonly used in the lithium secondary battery, it can be used without restriction, especially, preferably, for the ion movement of the electrolyte, the impedance is low and there is excellent electrolyte moisture-containing capacity. Specifically, a porous polymer film can be used, for example, a porous polymer film prepared by polyolefin polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers or their two or more layers of stacked structures. In addition, a common porous non-woven fabric can also be used, for example, a non-woven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc. In addition, in order to ensure heat resistance or mechanical strength, a separation membrane coated with a ceramic component and a polymer substance can also be used, which can be selectively used with a single layer or multilayer structure.
[0156] Furthermore, examples of the electrolyte used in the present invention include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in preparing lithium secondary batteries.
[0157] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0158] As the above-mentioned organic solvent, any organic solvent that can act as a medium for the movement of ions involved in the electrochemical reaction of the battery can be used without limitation. Specifically, as the above-mentioned organic solvent, ester solvents such as methylacetate, ethylacetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (EPC), etc. can be used. Carbonate solvents such as nate, PC, etc.; alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (r is a straight-chain, branched or cyclic hydrocarbon group with 2 to 20 carbon atoms, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolane, etc. Among them, carbonate solvents are preferred, and more preferably, a mixture of cyclic carbonates (such as ethylene carbonate or propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve the charge and discharge performance of the battery, and low-viscosity linear carbonate compounds (such as ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate, etc.). In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, excellent electrolyte performance can be shown.
[0159] The above-mentioned lithium salt can be used without limitation as a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the above-mentioned lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. Preferably, the concentration of the above-mentioned lithium salt is used in the range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore, excellent electrolyte performance can be shown, and lithium ions can be effectively moved.
[0160] When the electrolyte used herein is a solid electrolyte, for example, a solid inorganic electrolyte such as a sulfide solid electrolyte, an oxide solid electrolyte, a nitride solid electrolyte, or a halide solid electrolyte can be used, and preferably a sulfide solid electrolyte can be used.
[0161] As the material of the sulfide solid electrolyte, a solid electrolyte containing Li, an X element (wherein X is at least one selected from P, As, Sb, Si, Ge, Sn, B, Al, Ga and In) and S can be used. Examples of the above-mentioned sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S-LiX (wherein X is a halogen element such as I or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (wherein m and n are integers, Z is Ge, Zn or Gam), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (wherein p and q are integers, and M is P, Si, Ge, B, Al, Ga or In), etc.
[0162] The solid electrolyte, preferably a sulfide-based solid electrolyte, may be in an amorphous state, may be in a crystalline state, or may be in a mixed state of the amorphous state and the crystalline state.
[0163] Examples of materials for oxide-based solid electrolytes include Li7La3Zr2O 12 , Li 7-x Ln3Z 1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, Li3+x PO 4-x N x (LiPON), Li 2+2x Zn 1-x GeO4(LISICON), etc.
[0164] The solid electrolyte may be arranged between the positive electrode and the negative electrode as a separate layer (solid electrolyte layer). In addition, the solid electrolyte may be partially contained in the positive electrode active material layer of the positive electrode independently of the solid electrolyte layer, or the solid electrolyte may be partially contained in the negative electrode active material layer of the negative electrode independently of the solid electrolyte layer.
[0165] In addition to the above electrolyte components, the electrolyte may further include one or more additives such as halogenated alkylene carbonate compounds such as bisfluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol or aluminum chloride, etc., for the purpose of improving the life characteristics of the battery, inhibiting the reduction of the battery capacity, and increasing the discharge capacity of the battery. In this case, the above additives may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.
[0166] As described above, the lithium secondary battery containing the positive electrode active material of the present invention stably shows excellent discharge capacity, output characteristics and life characteristics, and can therefore be used in portable devices such as mobile phones, notebook computers, digital cameras, and electric vehicles such as hybrid electric vehicles (HEV).
[0167] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a prismatic shape, a pouch shape, a coin shape, etc. Also, preferably, the lithium secondary battery can be used not only as a battery cell used as a power source for small devices, but also as a unit battery of a medium or large battery module including a plurality of battery cells.
[0168] According to another aspect of the present invention, a battery module including the above-mentioned lithium secondary battery as a unit cell and / or a battery pack including the same may be provided.
[0169] The battery module or the battery pack can be used as a power tool; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle and a plug-in hybrid electric vehicle (PHEV); or a power source for one or more medium or large devices in a power storage system.
[0170] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples.
[0171] Preparation Example 1. Preparation of positive electrode active material
[0172] Comparative Example 1
[0173] (a) Precursor preparation
[0174] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co 0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0175] (b) First heat treatment
[0176] The hydroxide precursor obtained in step (a) is heat-treated in an O2 atmosphere at 550°C for 5 hours and then furnace-cooled to obtain an oxide precursor.
[0177] (c) Second heat treatment
[0178] A mixture is prepared by mixing the precursor in an oxide state obtained in step (b) and LiOH (lithium / metal molar ratio = 1.22) as a lithium raw material.
[0179] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 750° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0180] The BET specific surface area of the above-mentioned final product (calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mino II of BEL Co., Ltd., Japan) was measured to be 3.30 m2 / g.
[0181] Comparative Example 2
[0182] (a) Precursor preparation
[0183] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co 0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0184] (b) First heat treatment
[0185] The hydroxide precursor obtained in step (a) is heat treated in an O2 atmosphere at 550°C for 5 hours and then furnace cooled to obtain an oxide precursor.
[0186] (c) Second heat treatment
[0187] The mixture is prepared by mixing the precursor in an oxide state obtained in step (b), LiOH (lithium / metal molar ratio=1.22) and LiF (weighed to 2.0 mol % based on the entire mixture) as lithium raw materials.
[0188] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 750° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0189] The BET specific surface area of the above-mentioned final product (calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mino II of BEL Co., Ltd., Japan) was measured to be 2.24 m 2 / g.
[0190] Comparative Example 3
[0191] A positive electrode active material was prepared in the same manner as in Comparative Example 1 except that LiF was used in an amount of 3.0 mol % based on the entire mixture in the above step (c).
[0192] The BET specific surface area (calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-minoII of BEL Corporation of Japan) of the final product obtained in Comparative Example 3 was measured to be 1.55 m 2 / g.
[0193] Comparative Example 4
[0194] (a) Precursor preparation
[0195] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co 0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0196] (b) First heat treatment
[0197] The hydroxide precursor obtained in step (a) is heat treated in an O2 atmosphere at 550°C for 5 hours and then furnace cooled to obtain an oxide precursor.
[0198] (c) Second heat treatment
[0199] The precursor in an oxide state obtained in step (b), LiOH (lithium / metal molar ratio=1.22) and LiF (weighed to 1.0 mol % based on the entire mixture) as lithium raw materials are mixed to prepare a mixture.
[0200] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 825° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0201] The BET specific surface area of the final product (calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-mino II of BEL Co., Ltd., Japan) was measured to be 1.42 m 2 / g.
[0202] Comparative Example 5
[0203] (a) Precursor preparation
[0204] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0205] (b) First heat treatment
[0206] The mixture is prepared by mixing the precursor in the hydroxide state obtained in step (a), LiOH (lithium / metal molar ratio=1.22) and LiF (weighed to 1.0 mol % based on the entire mixture) as lithium raw materials.
[0207] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 750° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0208] The BET specific surface area of the final product (calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-mino II of BEL Co., Ltd., Japan) was measured to be 1.57 m 2 / g.
[0209] Comparative Example 6
[0210] (a) Precursor preparation
[0211] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co 0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0212] (b) First heat treatment
[0213] The hydroxide precursor obtained in step (a) is heat treated in an O2 atmosphere at 550°C for 5 hours and then furnace cooled to obtain an oxide precursor.
[0214] (c) Second heat treatment
[0215] The precursor in an oxide state obtained in step (b), LiOH (lithium / metal molar ratio=1.22) and LiF (weighed to 1.0 mol % based on the entire mixture) as lithium raw materials are mixed to prepare a mixture.
[0216] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 705° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0217] The BET specific surface area of the above-mentioned final product (calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mino II of BEL Co., Ltd., Japan) was measured to be 3.60 m 2 / g.
[0218] Example 1
[0219] (a) Precursor preparation
[0220] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co 0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0221] (b) First heat treatment
[0222] The hydroxide precursor obtained in step (a) is heat treated in an O2 atmosphere at 550°C for 5 hours and then furnace cooled to obtain an oxide precursor.
[0223] (c) Second heat treatment
[0224] The precursor in an oxide state obtained in step (b), LiOH (lithium / metal molar ratio = 1.22) and LiF (weighed to 0.5 mol % based on the entire mixture) as lithium raw materials are mixed to prepare a mixture.
[0225] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 750° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0226] The BET specific surface area of the final product (calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77 K) using BELSORP-mino II of BEL Corporation, Japan) was measured to be 3.09 m 2 / g.
[0227] Example 2
[0228] A positive electrode active material was prepared in the same manner as in Example 1 except that 1.0 mol % of LiF was used in the above step (c) based on the entire mixture.
[0229] The BET specific surface area of the final product obtained in Example 2 (calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-minoII of BEL Corporation of Japan) was measured to be 2.72 m 2 / g.
[0230] Example 3
[0231] A positive electrode active material was prepared in the same manner as in Example 1 except that 1.5 mol % of LiF was used in the above step (c) based on the entire mixture.
[0232] The BET specific surface area of the final product obtained in Example 3 (calculated from the nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP-minoII of BEL Corporation of Japan) was measured to be 2.57 m 2 / g.
[0233] Example 4
[0234] (a) Precursor preparation
[0235] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co 0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0236] (b) First heat treatment
[0237] The hydroxide precursor obtained in step (a) is heat treated in an O2 atmosphere at 550°C for 5 hours and then furnace cooled to obtain an oxide precursor.
[0238] (c) Second heat treatment
[0239] The precursor in an oxide state obtained in step (b), LiOH (lithium / metal molar ratio=1.22) and LiF (weighed to 1.0 mol % based on the entire mixture) as lithium raw materials are mixed to prepare a mixture.
[0240] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 775° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0241] The BET specific surface area of the above-mentioned final product (calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mino II of BEL Co., Ltd., Japan) was measured to be 2.46 m 2 / g.
[0242] Example 5
[0243] (a) Precursor preparation
[0244] An aqueous solution of NiSO4·6H2O, CoSO4·6H2O and MnSO4·H2O mixed in a molar ratio of 40:2:58, NaOH and NH4OH were added to the reactor and stirred. The temperature in the reactor was maintained at 50°C, and the precursor synthesis reaction was carried out while introducing gases containing N2 and O2 into the reactor. After the reaction was completed, the Ni 0.4 Co 0.02 Mn 0.58 (OH)2 is a hydroxide precursor.
[0245] (b) First heat treatment
[0246] The hydroxide precursor obtained in step (a) is heat treated in an O2 atmosphere at 550°C for 5 hours and then furnace cooled to obtain an oxide precursor.
[0247] (c) Second heat treatment
[0248] The precursor in an oxide state obtained in step (b), LiOH (lithium / metal molar ratio=1.22) and LiF (weighed to 1.0 mol % based on the entire mixture) as lithium raw materials are mixed to prepare a mixture.
[0249] Next, a heat treatment was performed in an O 2 atmosphere at a temperature of 800° C. for 8 hours, followed by furnace cooling, to obtain a positive electrode active material containing a lithium manganese-based oxide as a final product.
[0250] The BET specific surface area of the above-mentioned final product (calculated from the nitrogen adsorption at liquid nitrogen temperature (77K) using BELSORP-mino II of BEL Co., Ltd., Japan) was measured to be 1.72 m 2 / g.
[0251] Preparation Example 2. Fabrication of a lithium secondary battery (half-cell)
[0252] 90 wt % of each positive electrode active material prepared according to Preparation Example 1, 4.5 wt % of carbon black, and 5.5 wt % of PVDF binder were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode slurry.
[0253] The positive electrode slurry was uniformly coated on an aluminum thin film with a thickness of 15 μm, and vacuum dried at 135° C., thereby preparing a positive electrode for a lithium secondary battery having a positive electrode active material layer formed thereon.
[0254] Relative to the above-mentioned positive electrode, lithium foil is used as a counter electrode, a porous polyethylene film (Celgard 2300, thickness: 25μm) is used as a separation membrane, and an electrolyte solution containing LiPF6 at a concentration of 1.15M in a solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate mixed in a volume ratio of 2:4:4 is used to prepare a half-cell.
[0255] Experimental Example 1. XRD analysis of positive electrode active material
[0256] X-ray diffraction (XRD) analysis was performed on each positive electrode active material prepared according to Preparation Example 1, and diffraction peaks appearing in the 2θ=18°~19° region and in the 2θ=44°~45° region were detected from the positive electrode active material, and the full width at half maximum (FWHM) of the diffraction peak was calculated. XRD analysis was performed using a Bruker D8 Advance diffractometer.
[0257] The above XRD analysis results are shown in Table 1 below.
[0258] Table 1
[0259] Classification <![CDATA[FWHM a ]]> <![CDATA[FWHM b ]]> <![CDATA[FWHM b / FWHM a ]]> Comparative Example 1 0.221 0.566 2.561 Comparative Example 2 0.189 0.641 3.392 Comparative Example 3 0.192 0.777 4.047 Comparative Example 4 0.223 0.54 2.422 Comparative Example 5 0.24 0.417 1.738 Comparative Example 6 0.237 0.614 2.592 Example 1 0.205 0.516 2.517 Example 2 0.198 0.512 2.586 Example 3 0.191 0.509 2.665 Example 4 0.17 0.41 2.432 Example 5 0.14 0.31 2.214
[0260] -FWHM a : Full width at half maximum of the diffraction peak appearing in the region of 2θ = 18° to 19°
[0261] -FWHM b : Full width at half maximum of the diffraction peak appearing in the region of 2θ = 44° to 45°
[0262] Referring to the results in Table 1 above, it can be confirmed that the full width at half maximum of the diffraction peaks appearing in the 2θ=18°~19° and 2θ=44°~45° regions of the positive electrode active materials according to Examples 1 to 5 is reduced compared to the positive electrode active material according to Comparative Example 1. However, it can be confirmed that the FWHM calculated from the positive electrode active materials according to Examples 1 to 5 is b / FWHM aSimilar to Comparative Example 1.
[0263] On the other hand, it can be confirmed that compared with the positive electrode active material according to Comparative Example 1, the half-maximum full width of the diffraction peak appearing in the 2θ=18°~19° region of the positive electrode active materials according to Comparative Examples 2 and 3 is reduced, while the half-maximum full width of the diffraction peak appearing in the 2θ=44°~45° region is increased.
[0264] In addition, it can be confirmed that since the positive electrode active material according to Comparative Example 4 is at a second heat treatment temperature greater than or equal to the eutectic point based on the LiF-LiOH binary phase diagram, LiF decomposes, so that most of the LiF is doped into the lithium manganese-based oxide instead of forming a coating containing LiF on the surface of the lithium manganese-based oxide, and therefore presents a diffraction peak with a half-maximum full width that is almost similar to that of the positive electrode active material of Comparative Example 1.
[0265] In addition, it can be confirmed that compared with the positive electrode active material according to Comparative Example 1, the half-maximum full width of the diffraction peak appearing in the 2θ=44°~45° region of the positive electrode active material according to Comparative Example 5 is reduced, while the half-maximum full width of the diffraction peak appearing in the 2θ=18°~19° region is increased. Compared with the positive electrode active material according to Comparative Example 1, the half-maximum full width of the diffraction peak appearing in the 2θ=18°~19° region and the half-maximum full width of the diffraction peak appearing in the 2θ=44°~45° region of the positive electrode active material according to Comparative Example 6 are both increased.
[0266] Experimental Example 2. Evaluation of electrochemical performance of lithium secondary battery (half-cell)
[0267] The lithium secondary battery (half-cell) prepared in Preparation Example 2 was subjected to a charge / discharge experiment using an electrochemical analyzer (Toyo, Toscat-3100) at 25°C, a voltage range of 2.5 V to 4.7 V, and a discharge rate of 2.0 C / 0.2 C to measure the initial charge capacity and rate performance (discharge capacity retention rate; rate capability, C-rate).
[0268] Furthermore, the same half button was charged / discharged 50 times at 2.0C / 0.2C in the driving voltage range of 2.5V to 4.7V at 25°C, and then the ratio of the discharge capacity at the 50th cycle relative to the initial discharge capacity (cycle capacity retention) was measured.
[0269] The above measurement results are shown in Table 2 below.
[0270] Table 2
[0271]
[0272] Referring to the evaluation results of the half-cells in Table 2 above, compared with the lithium secondary batteries using the positive electrode active materials according to Comparative Examples 1 to 6, the initial charge capacity, initial discharge capacity and rate performance of the lithium secondary batteries using the positive electrode active materials according to Examples 1 to 5 are comprehensively improved.
[0273] In particular, in the case of the positive electrode active material according to Comparative Example 3, since the content of LiF used before the second heat treatment is excessively increased, the BET specific surface area of the positive electrode active material is excessively reduced, and thus it is predicted that the rate performance is reduced compared with the positive electrode active material according to Comparative Example 1. In addition, in the case of the positive electrode active material according to Comparative Example 4, since the second heat treatment temperature becomes too high, the BET specific surface area of the positive electrode active material is excessively reduced, and thus it is predicted that the rate performance is reduced compared with the positive electrode active material according to Comparative Example 1.
[0274] In the case of the cathode active material according to Comparative Example 5, when the same second heat treatment temperature is applied, the BET specific surface area is too low compared to the case of using an oxide precursor, and therefore it is expected that the rate performance is lower than that of the cathode active material using an oxide precursor.
[0275] Experimental Example 3. Analysis of Residual Lithium in Positive Electrode Active Material
[0276] The residual lithium (lithium impurity) content in the positive active material prepared according to Preparation Example 1 was analyzed by pH titration. As a pH titration method, the residual lithium (lithium impurity) content was measured by pH titration of the above-mentioned positive active material with the amount of 0.1N HCl used until the pH value reached 4. Specifically, 5 g of each positive active material prepared according to Preparation Example 1 was added to 100 ml of deionized water (DIW), stirred for 15 minutes and filtered, 50 ml of the filtered solution was taken, and 0.1 M HCl was added thereto to measure the HCl consumption according to the pH change, and the content of LiOH and Li2CO3 was calculated.
[0277] On the other hand, if a coating layer containing LiF is present on the surface of the positive electrode active material (lithium manganese-based oxide) prepared according to Preparation Example 1, LiF reacts with deionized water to generate HF during pH titration, thereby causing a reversible reaction in which HF decomposes Li2CO3 dissolved in the deionized water.
[0278] <Li2CO3 decomposition reaction of LiF>
[0279] LiF+H2O→LiOH+HF
[0280] 2HF+Li2CO3→2LiF+CO2+H2O
[0281] That is, as the content of LiF on the surface of the positive electrode active material (lithium manganese-based oxide) increases, the content of LiOH measured during pH titration increases, while the content of Li2CO3 decreases. Therefore, if LiF is decomposed and doped into the lithium manganese-based oxide rather than coated on the surface of the lithium manganese-based oxide during the heat treatment process, the content changes of LiOH and Li2CO3 according to the above-mentioned reversible reaction are not observed.
[0282] The above residual lithium analysis results are shown in Table 3 below.
[0283] Table 3
[0284] Classification LiOH(ppm) <![CDATA[Li2CO3(ppm)]]> Total residual lithium (ppm) Comparative Example 1 1669 860 2529 Comparative Example 4 1774 748 2522 Example 1 1938 617 2555 Example 2 2262 517 2779
[0285] Referring to the results in Table 3 above, it can be confirmed that the content of LiOH in the positive electrode active materials according to Examples 1 and 2 increases, the content of Li2CO3 decreases, and the total amount of residual lithium remains almost unchanged when compared with the positive electrode active material according to Comparative Example 1. In addition, when comparing the positive electrode active material according to Example 1 and the positive electrode active material according to Example 2, it can be confirmed that as the content of LiF in the positive electrode active material increases, the content of LiOH further increases, and the content of Li2CO3 further decreases.
[0286] On the other hand, it can be confirmed that since the positive electrode active material according to Comparative Example 4 is subjected to the second heat treatment at a temperature greater than or equal to the eutectic point based on the LiF-LiOH binary phase diagram, LiF decomposes, and most of the LiF is doped into the lithium manganese-based oxide instead of forming a coating containing LiF on the surface of the lithium manganese-based oxide, the content change of Li2CO3 is less than that of Examples 1 and 2.
[0287] Experimental Example 4. XPS Analysis of Positive Electrode Active Material
[0288] The lithium manganese-based oxides selected from the respective positive electrode active materials according to Example 1 and Example 2 were subjected to XPS analysis to measure the content of the target element F contained in the above lithium manganese-based oxides.
[0289] Specifically, using the XPS depth profile analysis method (ion energy: 2000eV, spot size: 200μm), while gradually increasing the etching time on the surface of the above-mentioned lithium manganese-based oxide, the change in the content of the target element, namely fluorine, from the surface portion of the above-mentioned lithium manganese-based oxide (secondary particles) toward the above-mentioned lithium manganese-based oxide (secondary particles) is measured.
[0290] Refer to the XPS analysis results shown above Figure 1 , it can be confirmed that fluorine exists at a high concentration on the surface of the lithium manganese-based oxide contained in the positive electrode active material according to Example 1 and Example 2. The above results indicate that a LiF coating is formed on the surface of the lithium manganese-based oxide contained in the positive electrode active material according to Example 1 and Example 2. In addition, it can be confirmed that the concentration of fluorine decreases as the etching time increases. The above results indicate that LiF diffuses from the surface portion to the center portion of the above lithium manganese-based oxide along the grain boundary, thereby forming a gradient in which the fluorine concentration decreases.
[0291] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.
Claims
1. A positive electrode active material, characterized in that: include: Lithium manganese-based oxide, formed by solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group; and A coating portion exists on at least a portion of the surface of the lithium manganese-based oxide; The coating portion includes fluorine, When the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα radiation, the full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ=18° to 19° is a The full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ=44° to 45° is greater than or equal to 0.14 and less than 0.
221. b Greater than or equal to 0.31 and less than 0.
641.
2. The positive electrode active material according to claim 1, characterized in that When the positive electrode active material is subjected to X-ray diffraction analysis using Cu-Kα radiation, the full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ=44° to 45° is b The full width at half maximum (FWHM) of the diffraction peak appearing in the region of 2θ = 18° to 19° a Ratio FWHM b / FWHM a Greater than 1.738 and less than or equal to 2.
665.
3. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide contains lithium, manganese and a transition metal.
4. The positive electrode active material according to claim 1, characterized in that The coating portion includes LiF.
5. The positive electrode active material according to claim 1, characterized in that In the positive electrode active material, the content of LiF is 0.5 mol % to 1.5 mol %.
6. The positive electrode active material according to claim 1, characterized in that The average thickness of the coating portion is 5 nm to 30 nm. The fluorine content in the coating portion is 2 atomic % to 10 atomic %.
7. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide exists in the form of secondary particles formed by agglomeration of a plurality of primary particles. The LiF concentration on the surface of the secondary particle is higher than the LiF concentration in the center of the secondary particle.
8. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide exists in the form of secondary particles formed by agglomeration of a plurality of primary particles. There is a gradient in which the fluorine concentration decreases from the surface portion of the secondary particle toward the center portion of the secondary particle along the grain boundary between the primary particles.
9. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1: [Chemical formula 1] He(He a M1 x M2 y )O 2-b X b (in, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, X is a halogen that can replace at least a part of the oxygen present in the lithium manganese-based oxide, <a≤0.7、0≤b≤0.1、0<x≤1、0≤y<1、0<x+y≤1)。 10. The positive electrode active material according to claim 1, characterized in that The lithium manganese-based oxide is represented by the following chemical formula 1-1: [Chemical formula 1-1] rLi2MnO 3-c X' c ·(1-r)Li a' M1 x' M2 y' O 2-b' X b' (Wherein, M1 is at least one selected from Ni and Mn, M2 is at least one selected from Ni, Mn, Co, Al, P, Nb, B, Si, Ti, Zr, Ba, K, Mo, Fe, Cu, Cr, Zn, Na, Ca, Mg, Pt, Au, Eu, Sm, W, Ce, V, Ta, Sn, Hf, Gd, Y, Ru, Ge and Nd, and M2 and M1 do not repeat, X and X' are each independently a halogen capable of replacing at least a portion of the oxygen present in the lithium manganese-based oxide, 0 <r≤0.7、0≤c≤0.1、0<a'≤1、0≤b'≤0.1、0<x'≤1、0≤y'<1、0<x'+y'≤1)。 11. The positive electrode active material according to claim 1, characterized in that The BET specific surface area of the positive electrode active material is greater than or equal to 1.6 m 2 / g and less than or equal to 3.2m 2 / g.
12. A positive electrode, characterized in that: The positive electrode active material comprises the positive electrode active material according to any one of claims 1 to 11.
13. A lithium secondary battery, characterized in that: The positive electrode according to claim 12 is used.